Exploring the Role of Early Childhood Education in Shaping Children's Future Development - Rumbidzai, Tatenda; Achebe, Mugabe (Educia Journal, 2023)
Early childhood education (ECE) serves as the cornerstone of a child’s holistic development, encompassing cognitive, emotional, and social dimensions. This qualitative study investigates the potential of ECE as a golden foundation for future development, emphasizing its role in character building, skill development, and the integration of innovative teaching methods. Using a phenomenological approach, data were collected through semi-structured interviews and focus group discussions with 12 participants, including educators, parents, and policymakers with significant experience in early childhood education. Findings reveal that play-based and inquiry-driven learning methods effectively foster critical thinking and problem-solving skills, while character-focused activities nurture empathy, communication, and self-regulation. Collaboration between teachers and parents emerges as a pivotal factor in creating a unified and supportive learning environment. Additionally, the study highlights the balanced use of technology in ECE, identifying it as a tool for enhancing creativity and engagement when implemented ethically and responsibly. This research addresses gaps in existing literature by providing a comprehensive understanding of ECE’s multidimensional impact and offering actionable insights into the integration of technology, parental collaboration, and character education. The findings underscore ECE's critical role in equipping children with the skills and resilience necessary to navigate a dynamic and interconnected world.